Testing the Design and Implementation of Teaching Materials Developed for Writing Budget Reports Using Microsoft Excel Media - Sulindawati, Ni Luh Gede Erni (Jurnal Pendidikan Indonesia, 2020)
This study was conducted with the aim of finding out  the result of testing the design and implementation of teaching materials developed  for writing budget reports using Microsoft Excel media.  The study method used teaching material development that consists of the steps of (1) design validation, (2) design revision, (3) product try-out,  (4) product revision, and (5) use try-out. The design validation was done by asking   experts to evaluate the design.  The materials developed were in the form of syllabus, semester lesson plans, learning materials  which  contain practice problems, and worksheets, and assessment  rubric.  The subjects were students who enrolled in Budgeting Course. The instruments used were observation guide, interview guide, questionnaire, and learning achievement test.  The data were analyzed by using descriptive analysis by measuring the students’ learning achievement as shown in their scores in the process of learning to write budget reports. The evaluation was done based on the scores the students got from the process evaluation, attitude and participation, and tasks as well as   from the product evaluation as shown by the products written by the students.  The result of the experts’ judgment of the design showed that the design is very valid.  The implementation showed that the students’ learning achievement in writing budget reports using Microsoft Excel showed that  the mean scores for  attitude, participation, product evaluation can be categorized into  the very good category. Hence, these teaching materials can be used in the teaching process  for teaching  how to write budget reports.